Feedbacks: basic elements of technological support for the technical study of conducting for visually impaired students - Erickinson Bezerra de Lima; Gabriel Gagliano (Per Musi, 2021)
Aiming at technological development to support the technical-individual study of conducting for visually impaired students, in the present approach, the sequence of tests and their results is exposed, to survey the requirements for the constitution and programming of the Maestro v0.1 prototype — haptic and auditory feedbacks. Therefore, considering them as essential elements to provoke the corrective action of the technical gesture of conducting to the student. The methodological procedure used is based on technological development centered on the user, based on Human-Computer-Interaction. To perform the usability tests, 25 visually impaired students from EMUFRN participated, who interacted with the stimuli of the proposed feedbacks, and printed their reactions in questionnaires. Finally, this article shows, through a theoretical and practical articulation, the baseline architecture of a prototype, which can provide the individual technical practice of conducting for visually impaired students.